Structure and Properties of the Surface Layer of B4C Ceramic Treated with an Intense Electron Beam; Inorganic Materials: Applied Research; Vol. 9, iss. 3 - Ivanov Yu. F. Yury Fedorovich; Khasanov O. L. Oleg Leonidovich; Petyukevich M. S. Mariya Stanislavovna; Smirnov G. V. Gennady Vasiljevich; Bikbaeva Z. G. Zulfa Gadilzanovna; Teresov A. D. Anton Dmitrievich; Kalashnikov M. P. Mark Petrovich; Tolkachev O. S. Oleg Sergeevich (2018, 2018)
Title screen